Antioxident status and metabolic profile of goats during pregnancy and lactation - Cynthia Jose (Department of Veterinary Biochemistry,College of Veterinary and Animal Science, 2010)
The present study was undertaken with the objective to assess the changes in antioxidant status indicators and metabolic profile of goats during pregnancy and lactation and to evolve any possible relationship between antioxidant markers and other relevant blood parameters. The study was carried out in 33 adult healthy female Malabari and crossbred goats aged between 3 to 6 years maintained at University Goat and Sheep Farm, College of Veterinary and Animal Sciences, Mannuthy during the period of March to November 2009. Blood samples were collected during early (between 40-60 d), mid (between 90-110 d) and advanced (between 130-150 d) period of gestation and on 7th, 45th and 70th d post-partum. Antioxidant and metabolic parameters were analyzed and were compared with dry and nonpregnant goats.